1981
DOI: 10.1063/1.92837
|View full text |Cite
|
Sign up to set email alerts
|

Electron bombardment induced conductivity in amorphous silicon

Abstract: Optically induced conductivity changes in dischargeproduced hydrogenated amorphous silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In order to obtain the electron bombardment for a photoconductor, a vacuum diode-type cold cathode device , was designed for exploring the EBIPC mechanism, which is shown schematically in Figure . A ZnS photoconductor has been used as a target in the image intensifier of camera tubes for use in low-light detection , and exhibits the advantages of high exciton binding energy, large-area fabrication, low cost, and ease of integration. , As such, it is of great promise for use in large-area and highly sensitive detectors. ZnO NW field emitters have been used in large-area flat panel vacuum devices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to obtain the electron bombardment for a photoconductor, a vacuum diode-type cold cathode device , was designed for exploring the EBIPC mechanism, which is shown schematically in Figure . A ZnS photoconductor has been used as a target in the image intensifier of camera tubes for use in low-light detection , and exhibits the advantages of high exciton binding energy, large-area fabrication, low cost, and ease of integration. , As such, it is of great promise for use in large-area and highly sensitive detectors. ZnO NW field emitters have been used in large-area flat panel vacuum devices.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the enhanced light response performance was associated with the electron bombardment from the cold cathode and its influence on the ZnS photoconductor. Early studies also suggested that the conductivity of a semiconductor could be enhanced by electron bombardment. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations